2018
DOI: 10.5121/ijcsa.2018.8301
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Fruit Recognition Based on DCNN for Commercial Source Trace System

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 16 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…In the work, it is reported that in the context of fruit recognition system SVM classifier works far better than other classifiers. The objective of the research [6] is to recognize the fruit using probability mechanism algorithm. Although they achieved good accuracy, the segmentation technique and feature set are not mentioned.…”
Section: Comparative Analysis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work, it is reported that in the context of fruit recognition system SVM classifier works far better than other classifiers. The objective of the research [6] is to recognize the fruit using probability mechanism algorithm. Although they achieved good accuracy, the segmentation technique and feature set are not mentioned.…”
Section: Comparative Analysis Of Resultsmentioning
confidence: 99%
“…Hussain et al [6] proposed an algorithm based on deep convolution neural network for fruit recognition where their contribution is to build a database of fruit image of only 15 categories which is very few compared with the huge categories of fruits and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deep learning frameworks achieved excellent performance in many fields [75], [80]. Researchers in image steganography and steganalysis also demonstrated to explore the capability of deep learning algorithms in various key areas of multimedia security.…”
Section: Image Steganalysis Based On Deep Learningmentioning
confidence: 99%
“…Hussain, I., He, Q. and Chen, Z. [8] developed a system using deep convolutional neural network model to extract fruit image features and implement classification. Sriram, R., M, A. T. and Girija, P. J.…”
Section: Introductionmentioning
confidence: 99%